Microalgal Schizochytrium limacinum Biomass Improves Growth and Filet Quality When Used Long-Term as a Replacement for Fish Oil, in Modern Salmon Diets - Katerina, Kousoulaki; Berge, Gerd Marit; Turid, Mørkøre; Aleksei, Krasnov; Grete, Baeverfjord; Trine, Ytrestøyl; Mats, Carlehög; John, Sweetman; Bente, Ruyter (Frontiers in Marine Science, 2020)
Aquaculture contributes to global food security but sustainable aquaculture development in terms of biodiversity impacts requires the establishement of viable solutions in replacement of the fisheries-based components in aquafeeds. In the current work, pit-tagged Atlantic salmon individuals were grown, from fresh water (18g body weight) to salt water in tanks (up to 800g body weight), on diets with low fish meal (10%) and 1-1.25% total n-3 LC-PUFA levels balanced acccross the experimental diets. Dietary n-3 LC-PUFAs were supplemented by 1) fish oil (FO), 2) Schyzochytrium limacinum biomass (ScB) or 3) a mix of the two (FO/ScB). Further, the fish from all treatments were mixed and redistributed in sea cages reared to slaughter (ca. 3kg body weight) on either FO or ScB. As fish oil was rich in both EPA and DHA and ScB was rich in DHA ands nearly devoid of EPA, the experimental diets differed significantly in DHA/EPA ratio (0.8 vs 10.5 in average for FO and ScB, respectively). ScB treatment fish grew to significantly higher body weight in the end of the experiment (2.8kg vs 3.3kg, for FO and ScB, respectively) but similar FCR, survival rate and biometric indexes as compared to the FO groups. ScB fish contained higher levels of EPA+DHA in the fillet but lower in the liver, and better fillet pigmentation already from the tank phase of the experiment as determined chemically, by salmonfan and a trained sensory panel, and lower prevalence of melanin spots at slaughter. The trained sensory panel found no differences in flavor or odour in the fillets from the different dietary groups, however fillets in the FO group were percieved as softer and juicier compared to ScB. The pre-diets up to 800 g body weight had minor effects on fish performance. Global transcriptomics in liver and intestinal tissues revealed significant dietary effects on the expression of immune modulating, as well as ion, lipid, protein and xenobiotic metabolism genes.